PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI PLATFORM SHOPEE DI SAAT PANDEMI COVID-19 : (Studi Kasus: Konsumen Shopee di Magelang, Jawa Tengah) - Arzan Alawi; Budi Rahardjo (Transpublika Publisher, 2022)
The COVID-19 pandemic has changed people's habits, especially shopping habits, during a pandemic like this, online transactions are very popular because they are easy and practical. In winning the competition, it is necessary to improve strategies, as is done by E-commerce in Indonesia by using promotion and price strategies so as to increase consumer buying interest. This study was conducted to find out and understand the relationship between promotions and prices with purchasing decisions through Shopee during the Covid-19 pandemic in Magelang, Central Java. This research data is primary data distributing questionnaires with purposive sampling method. The approach method used is a quantitative method using 100 samples. The data analysis technique used validity test, reliability test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), multiple linear regression analysis, T test, F test and Coefficient of Determination Test (R2). Data processing using SPSS version 25.0. This study shows that promotions and prices partially and simultaneously influence purchasing decisions through Shopee during the Covid-19 Pandemic in Magelang, Central Java. The results of the study have implications for e-commerce in Indonesia to increase promotions such as using boybands as brand ambassadors to make it more crowded. And, pay more attention to the prices that are made in order to attract customers to shop. By implementing this strategy, it is expected that consumer purchasing decisions can improve.